Multimedial environment for the teaching of osteoarticular surgical pathologies (Veterinary Science, 2020)
The authors inform the results of the students’ assessment of a digital multimedia which offers digital specimens with surgical pathologies of osteoarticular system of domestic animals. Specimens belonging to the collection of the subject Surgical Technique and Pathology (Faculty of Veterinay Science – National University of La Pampa) were digitalized and integrated to a digital environment. Forty-eight students who had already done the subject participated voluntarily in the experience. They explored each specimen from different angles using the mouse to freely turn and amplify the images. They then registered their impressions in a survey in which they valued the degree of similarity between the virtual specimens and the real ones, the sensibility of response of the virtual specimens to the mouse movements, the identification of lesions and the degree of difficulty in identifying them. The results were analyzed with a descriptive statistical method. The surveyed students were able to identify the osteoarticular lesions and mentioned the similarity between the virtual and real specimens. The digital multimedia was positively evaluated by the students as a valuable pedagogical tool. The authors consider that this pedagogical tool responds to the student`s interests and technological abilities, with which they are already familiar.
Keywords: Multimedia tool; virtual specimen; teaching-learning process